Robot-Assisted Transcervical Esophagectomy for Thoracic Esophageal Carcinoma - Fujita, Takeo (Journal of chest surgery, 2025)
Surgical approaches for thoracic esophageal cancer have evolved from invasive open procedures to minimally invasive techniques such as thoracoscopic and robot-assisted surgery. While robotic surgery offers improved precision and visualization, it still relies on single-lung ventilation and may not significantly reduce postoperative complications. Recently, transcervical esophagectomy (TCE) using a mediastinoscope has emerged as a promising alternative, enabling esophageal resection and lymphadenectomy via the neck without thoracic incisions. However, challenges such as recurrent laryngeal nerve palsy and limited reproducibility persist. Robot-assisted TCE addresses these issues by improving precision and reducing interference in the narrow mediastinum. Early studies, including the authors' pilot work, have shown encouraging results. Despite its potential, comprehensive data on the short-term outcomes and safety of this technique remain limited. This study aims to introduce robot-assisted TCE for patients with thoracic esophageal carcinoma and compare its clinical benefits with those of transthoracic robot-assisted esophagectomy, thereby clarifying its role in the evolving field of esophageal cancer surgery.